Potential diagnostic assay for cystinuria by capillary electrophoresis coupled to mass spectrometry - Barbosa, Camila G. [UNIFESP] (2013)
Cystinuria is an autosomal recessive genetic disorder characterized by abnormal intestinal and renal tubular transport of L-cystine as well as of L-lysine, L-arginine and L-ornithine. This leads to excessive urinary excretion of amino acids, with the formation of kidney stones caused by the low solubility of L-cystine in the urine. In this study, an analytical method for simultaneous determination of these four amino acids in urine by capillary electrophoresis coupled to electrospray ionization mass spectrometry (CE-ESI-MS) was developed and validated. Using standard solutions of L-cystine, L-lysine, L-arginine and L-ornithine, the amino acid detection limits by this method were 114.2, 61.3, 72.7 and 86.7 µmol L-1. Standard solutions were injected in a silica capillary column (50 µm i.d. and 70 cm length) under 2 psi of pressure by 10 s. The separation occurred at 300 V cm-1, using 1.0 mol L-1 formic acid in 10% methanol in water as the background electrolyte. The method was applied to the urine of a patient clinically diagnosed as a cystinuria carrier, which revealed the presence of 900.5 ± 5, 600.0 ± 2, 700.2 ± 1 and 500.0 ± 3 µmol L-1 of amino acid, respectively, and 75.3 ± 1 µmol L-1 of creatinine. The CE-ESI-MS method described here for analyzing L-cystine and other cystinuria-related amino acids is a sensitive and reliable diagnostic tool for characterizing and monitoring this disease.